2001
DOI: 10.1128/aem.67.6.2469-2475.2001
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Specific Endophytic Bacterial Genotypes by Plants in Response to Soil Contamination

Abstract: Plant-bacterial combinations can increase contaminant degradation in the rhizosphere, but the role played by indigenous root-associated bacteria during plant growth in contaminated soils is unclear. The purpose of this study was to determine if plants had the ability to selectively enhance the prevalence of endophytes containing pollutant catabolic genes in unrelated environments contaminated with different pollutants. At petroleum hydrocarbon contaminated sites, two genes encoding hydrocarbon degradation, alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
184
1
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(197 citation statements)
references
References 58 publications
4
184
1
8
Order By: Relevance
“…Earlier results had indicated that growing plants on contaminated soil could selectively enhance the prevalence of endophytes containing the degradation pathways for specific pollutants 21 . After 21 d of growth without toluene, the plants were transferred to glass cuvettes containing toluene in the lower compartment at final concentrations of 0, 100, 500 or 1,000 mg/l.…”
Section: Selective Enrichment Of Endophytic Bacteria By Toluenementioning
confidence: 99%
“…Earlier results had indicated that growing plants on contaminated soil could selectively enhance the prevalence of endophytes containing the degradation pathways for specific pollutants 21 . After 21 d of growth without toluene, the plants were transferred to glass cuvettes containing toluene in the lower compartment at final concentrations of 0, 100, 500 or 1,000 mg/l.…”
Section: Selective Enrichment Of Endophytic Bacteria By Toluenementioning
confidence: 99%
“…Some examples include nitrogen fixation, antibacterial and antifungal activities, as well as plant growth promotion (Brooks et al, 1994;Berg et al, 2005;Tan et al, 2006;Rijavec et al, 2007). Other roles such as synthesis of novel chemicals, resistance to heavy metals and xenobiotic degration have been observed in isolated endophytes (Siciliano et al, 2001;Ryan et al, 2007). Importantly, it has been suggested that investigating the diversity of bacterial endophytes may lead us to identify novel drugs for treatment of diseases in humans, plants and animals (Strobel et al, 2004;Ryan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of a phytoremediation process depends mainly on the presence and activity of plant-associated microorganisms carrying degradation genes required for the enzymatic break-down of contaminants. The rhizosphere and plant endosphere have been reported to host pollutant-degrading bacteria (Siciliano et al, 2001;Andria et al, 2009;) and highly diverse alkane degrading bacteria containing alkane degrading genes have been isolated from the plant environment (Kaimi et al, 2007). Expression analysis of alkane monooxygenase (alkB) and a cytochrome P450 hydroxylase (CYP153 gene) indicated degradation in the rhizosphere as well as in the plant interior (Powell et al, 2006;Andria et al, 2009;Afzal et al, 2011).…”
Section: Introductionmentioning
confidence: 99%